Sociological analysis of psychophysical readiness of students of the social and legal institute for future professional activities - Isaev R.S.; Ponomarev V.V.; Shcherbakov E.S.; Petukhov K.G. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to substantiate and develop a sociological questionnaire for analyzing the psychophysical readiness of students for future professional activity; to identify students’ readiness for active work in the profession, based on the analytical material obtained. Methods and structure of the study. A sociological analysis based on a questionnaire survey was conducted in 2024 among 2nd-3rd year students of the Social and Legal Institute of Siberian Federal University in Krasnoyarsk. The sample size was 70 people. A questionnaire was developed in advance, including 9 questions related to the analysis of students’ psychophysical readiness for future professional activity. The developed sociological questionnaire was presented to students, who gave their written answers to the questions, on the basis of which a theoretical analysis of the psychophysical readiness of young people for active labor activity was carried out. Results and conclusions. The conducted sociological analysis revealed students’ attitudes toward the need to develop psychophysical readiness for future professional activity; their understanding of the concept of ‘psychophysical readiness’; the means and forms of developing psychophysical readiness identified by respondents; the general readiness of students for systematic physical education and sports activities to maintain psychophysical potential in the process of life.